Tariqah al-Tatbiqi li-Tarjamat Kutub al-Turath fi Mu'assasat Dirasat al-Qur'an wa Kitab al-Turath Surabaya - Moh Nurul Huda (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Arabic language has some effects for governing Islamic knowledge, furthermore the first source Islamic knowledge is al-Qur’an and al-Hadits that used arabic language. If we want to govern it, we must know arabic language. Usually turast book was studied in Islamic boarding school for understanding some religion knowledges from al-qur’an and al-hadits. For understanding turast book we have to pass transliteration process. It will be find the conclution from the Islamic knowledge. One of way to ease the student for transliting arabic books is tatbiqi methode. It’s combine arabic gramatical, learning vocabularies, and transliting process. The student not only learn the arabic gramatical, but also practice to translate arabic texts according to the principle was learned.